Advanced polymeric membrane technology for gas separation processes - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail (Penerbit UMPSA, 2023)
This book is designed to provide a comprehensive overview of the latest advancements in the field of polymeric membranes for gas separation applications. Gas separation has become a crucial process in various industries, ranging from energy production and environmental protection to food and beverage processing, pharmaceuticals, and more. Polymeric membranes have emerged as a promising solution for gas separation due to their unique properties, such as high selectivity, ease of fabrication, and cost-effectiveness. Over the past few decades, significant progress has been made in the development of advanced polymeric membrane materials, fabrication techniques, and characterization methods, leading to improved performance and expanded applications in gas separation processes.